Legal Political Policy In Resolving The Papua Conflict - Kossay, Methodius; Wahid, Eriyantouw (Journal Research of Social Science, Economics, and Management, 2022)
The Central Government’s policy for Papua has been periodically carried out since the integration of Papua until the enactment of Law No. 21 of 2001 concerning Special Autonomy for the Papua Province. However, since the 20th anniversary of the implementation of Law Number 2 of 2021, the second amendment to Law Number 21 of 2001 concerning Special Autonomy for the Papua Province, has so far not had a significant impact on development in Papua. The purpose of the research in this paper is to find out and analyze how legal political policies are to resolve conflicts. The research method that will be used in this study is a qualitative method, namely describing the facts with primary secondary and tertiary legal materials. This is caused by the various roots of the Papuan conflict that have not been resolved until now. Various policies under the Papua Special Autonomy Law and regulations in the form of Presidential Instructions, Presidential Regulations, Perdasi, Perdasus and sectoral regulations were issued using the Welfare Approach and the Security Approach model. However, it still does not have an impact, especially for the Indigenous Papuans (OAP) and does not reduce violent conflicts in the Land of Papua. The purpose of this study is to find out and analyze how legal political policies are in resolving the Papuan conflict. The research method that will be used in this study is a qualitative method with a normative type of research. The theory used in this study is the Theory of the Rule of Law, Theory of L.M. Friedman and the Theory of Justice. The result of the research is that the various policies of the Central Government for Papua in resolving the Papuan conflict have not been able to resolve the conflict in Papua. So one of the legal political policies that must be carried out is Peaceful Dialogue through negotiations. The product of the negotiations between the parties is a Memorandum of Understanding (MoU) as an agreement to end the conflict completely in the Land of Papua.